Pertimbangan Hakim Mengenai Kekuatan Mengikat Akta Pembagian Harta Bersama Berdasarkan Keadilan Distributif Aristoteles - Mahkota Fadia Bella Pradita; Anjar Sri Ciptorukmi Nugraheni (Indonesian Journal of Social Sciences and Humanities, 2026)
This study aims to analyze the judge’s legal considerations regarding the binding force of the deed of division of joint assets in Decision Number 38/Pdt.G/2020/PN Smn viewed from the perspective of Aristotle’s distributive justice. This study uses prescriptive and applied normative legal methods, with a statutory and conceptual approach. Data collection through literature studies. Types of legal materials include primary and secondary legal materials. Deductive analysis techniques and legal syllogism methods. The results of the study show that the legal considerations of the Panel of Judges are in line with applicable positive law, namely: (1) determination of the object of the dispute as joint assets based on Article 35 paragraph (1) of Law No. 1 of 1974; (2) recognition of the Deed of Statement of Division of Gono Gini Assets Number 41 as a legal instrument of choice for the parties after the divorce in accordance with Article 37 of Law No. 1 of 1974; (3) determination of the deed as authentic evidence with perfect evidentiary force referring to Article 1868 and Article 1870 of the Civil Code. The consistency of these considerations was affirmed up to the cassation level through the ne bis in idem decision. Overall, Decision Number 38/Pdt.G/2020/PN Smn has reflected the principle of justice through a combination of procedural justice and Aristotelian distributive justice. Procedural justice is realized through adherence to the principles of pacta sunt servanda and good faith as per Article 1338 of the Civil Code. Distributively, the decision provides proportional economic protection for children as vulnerable parties and recognizes the wife’s immaterial contribution. The judge also upheld corrective justice by rejecting the Plaintiff’s breach of contract to ensure the best interests of the children.